Donor-acceptor systems based on fullerene C60 and lipophilic meso-arylporphyrins - E. S. Zyablikova; N. A. Bragina; A. F. Mironov (Тонкие химические технологии, 2012)
In this paper we report the synthesis donor - acceptor systems based on fullerene C60 and lipophilic meso - arylporphyrins . The obtained conjugates were characterized by IR, UV-vis,1H,13C NMR spectroscopy and MALDI-TOF mass spectrometry. The fluorescence spectra of porphyrin–fullerene C60 donor-acceptor dyads were studied.